Effects of liquid ionic silver concentration on caspase-3 and p53mt expressions in the oral mucosal epithelium of Wistar rats - R. Aries Muharram; I. Istiati; Pratiwi Soesilawati (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Silver, especially oxidized silver, has been used as a medicine considered to have bactericidal properties. In the present day, ionic silver (Ag+) is also used in the manufacture of cosmetics, socks, food containers, detergents, sprays and other products to prevent the spread of germs. Unfortunately, ionic silver is assumed to be toxic not only to bacteria, but also to humans and the environment. Therefore, it is essential to identify the optimum dosage of ionic silver considered safe by investigating the effects of ionic silver concentration on cell death through activation of mutant p-53 expression by caspase 3 in the oral epithelium. Purpose: This research aimed to analyze the effects of concentrated liquid ionic silver (Ag+) on caspase-3 and mutant p53 expression in the oral mucosal epithelium. Methods: This research constituted a laboratory-based experimental study with posttest-only design. The research subjects consisted of 28 Wistar rats, divided into four treatment groups, namely; KK (with Aquadest), KP 1 (with 5% liquid ionic silver), KP 2 (with 10% liquid ionic silver) and KP 3 (with 15% liquid ionic silver). Each rat was then treated orally with 0.5ml of liquid ionic silver at fixed concentrations twice a day for seven days. The Wistar rats were then terminated and their tissue samples processed by means of histopathological and immunohistochemical staining examination. The monoclonal Caspase-3 and mutant p53 expressions in each group were evaluated with the data being tabulated and analyzed statistically. Results: Mutant p53 expression was also found in the control group. Moreover, the higher the concentration of liquid ionic silver, the greater the elevated Caspase-3 and mutant p53 expressions. Conclusion:  The concentration of liquid ionic silver plays an important role in elevating Caspase-3 and mutant p53 expressions.